(untitled) (Research, Society and Development, 2022)
This work presents environmental actions carried out in the project, entitled, Conscientization for Conservation: Environmental Education in the Charapucu State Park, being a project that emerged through management planning of the Institute for Forestry Development of Biodiversity of the state of Pará, having its dynamics based on actions that permeate traditional communities in a conservation unit. The objective is to systematize the actions that were carried out in the Charapucu State Park, being an Integral Protection Nature Conservation Unit located in the Pará Amazon, on Marajó Island, in the city of Afuá. Methodologically, this research has a qualitative scope because it involves studies of group social actions, in the case of a participatory action research, the project addresses lectures, educational actions, gymkhanas, puppet theater, educational playful games, construction of a suspended vegetable garden, among others. It concludes with the development of the project, which makes it possible to reach different audiences, currently approximately 2,500 people have been totaled in 15 schools in rural and urban areas and 12 rural communities, thus making it possible to work with schools and communities in the floodplain area, being a territory of difficult access where the exploitation of natural resources are the livelihood of local families.